Epidemiology of bacterial diseases of pome fruit trees caused by Pseudomonas syringae pv. syringae - Mansvelt, E. Lucienne (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D.) -- University of Stellenbosch, 1986.